Implementasi Pendidikan Agama Islam Berbasis Outcame Based Education (OBE) di Perguruan Tinggi Umum - Siti Masruroh; Shofa Shofia Hilabi (Jurnal Dirosah Islamiyah, 2022)
The purpose of this research is on the Islamic religious education model based on outcame based education in public universities, namely Islamic religious education which encourages students to continue to improve their abilities in the academic field, both cognitive, affective and psychomotor abilities so that they are able to integrate religious values ​​and technological advances so that they are easily accepted. in the field of work and in the community. With the purpose of this research, students have the ability to apply learning strategies independently, innovatively and creatively so that the achievement of the Outcame Based Education (OBE)-based Islamic religious education model is well achieved. The research method uses qualitative methods, data collection with online interviews and group discussions. discusses the Islamic religious education system in public universities. Keywords: Model, Outcame Based Education, Cognitive, Affective, Psychomotor